A group-based recidivist sentencing premium? The role of context and cohort effects in the sentencing of terrorist offenders. Issue 4 (December 2015) - Amirault, Joanna; Bouchard, Martin
Abstract: Despite recent interest in terrorism little is known about the sentencing of terrorist offenders, and the impact of cohort effects on the sentencing patterns of offenders over the course of a terrorist campaign remains virtually unexplored. The 'recidivist sentencing premium' states that offenders who continually engage in criminal activities should be sanctioned more harshly as their careers progress. Unknown, however, is whether a penalty is applied to first time terrorist offenders as a result of the campaign's collective criminal involvement. The current study analyzes changes in the sentencing outcomes of members of the Front de Liberation du Quebec ( n = 108) over the 10 years that the group was active. The findings indicate that context plays a role in both the actions and adjudication of offenders. Cohort effects are uncovered, and offenders sanctioned later in the campaign are generally sentenced more severely than those at the onset for similar offenses.